Intelligent Healthcare System using a Machine learning model to Predict Diseases - Stanley G, *Sharun T, *Satheesh Kumar B, Muthamil Sudar K, Nagaraj.P (International Journal of Advanced Science and Technology, 2020)
One of the most emerging technologies in recent times is Machine Learning. MachineLearning techniques provide various algorithms and machine learning models which helps machinesto understand the problems and derive solutions for the particular problem. We are also using thismachine learning techniques to create a model which helps us in the prediction of diseases. We areusing Logistic Regression algorithm in our machine learning model. We are using this machinelearning model which excels in analysing the given symptoms and predicting the diseases. We arecreating a user-friendly webpage which gets the input from the user and after receiving the inputs itconverts these inputs as test datasets and runs in our machine learning model. Then the predictedoutput is then displayed in the webpage as output. The output is also shows the severity of the diseaseand predicts which stage of the disease the user may be. Our model can be used to predict variousdiseases based on the users requirement. We are using Logistic Regression instead of LinearRegression to avoid the chances of overfitting or underfitting which may lead to inaccuratepredictions.There are number of algorithms and program to detect one disease at a time, but we arecreating an application which option to predict various diseases at the same page.